Customers Adaptation of E-banking services; extending TAM through Anthpmorphism in Saudi Arabia - Alqutub, Kholoud (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to investigate influence of perceived anthropomorphism, perceived ease of use, perceived usefulness, privacy concerns, as well as attitude on intention to adopt AI banking services. The research follows a positivistic and deductive reasoning approach, utilizing experimental techniques in a cross-sectional design. Data of 210 responses collected through a questionnaire distributed via Google Docs were analyzed using Smart PLS3. The results indicate that intention to adopt AI banking services is influenced by perceived anthropomorphism, perceived ease of use, perceived usefulness, and privacy concerns through attitude. Strong correlations among all variables were observed, highlighting the significant and positive impact of artificial intelligence on encouraging acceptance of advanced technology in banking sector in Kingdom of Saudi Arabia. Future research is recommended to test various other variables using the same research model in different countries. Practical implications include the need for senior managers and policymakers in financial institutions to formulate relevant policies and marketing strategies aligned with customer needs. This research study's primary objective is to prospect and examine factors impelling consumer adoption intentions of artificial intelligence in banking sector in Kingdom of Saudi Arabia.